Surfactant Adsorption Layers: Experiments and Modeling - Kovalchuk, V I; Aksenenko, E V; Schneck, E; Miller, R (Langmuir, 2023)
During recent years, great progress has been made in understanding the adsorption of surfactants at liquid interfaces. In addition to tensiometry, new efficient methodologies have been developed, in particular interfacial selective optical methods which allow direct access to the adsorbed amounts and interfacial layer compositions. In addition to these new experimental tools, the thermodynamic description by equations of state now allows one to provide a quantitative picture of surfactant interfacial layers. This is most notable for surfactant layers at water/oil interfaces. Additional knowledge about the structure of interfacial layers was gained through different types of molecular modeling. Improved interrelationships between these three aspects are the challenges for current and future work. Particular attention must be paid to dilational interfacial rheology studies, as these mechanical quantities are much more sensitive to small changes in the interfacial composition and structure.